Pengetahuan dan sikap suami behubungan dengan perilaku keluarga mandiri sadar gizi (kadarzi) di Kota Bandung Provinsi Jawa Barat - Misbakhudin Misbakhudin; Toto Sudargo; Muhammad Dawam Jamil (Jurnal Gizi Klinik Indonesia, 2008)
Background: A nutrition awareness of family (kadarzi) can be actualized through family empowerment by improving knowledge and attitude toward nutrition alert behavior. To implement the program of kadarzi needs a motivator, i.e. a husband as head of the family. The result of kadarzi mapping at Bandung Municipality in 2005 showed that 57.23% of families were not nutrition alert. Therefore, it is necessary to study the relationship between knowledge and attitude of husbands and behavior of kadarzi.Objective: To identify the relationship between knowledge and attitude of husbands and behavior of kadarzi.Method: The study was observational with cross sectional design using quantitative method. Analysed units were 378 households with husbands and wives as respondents. Location of the study was Bandung Municipality and samples were taken using multistage cluster technique. Data of knowledge and attitude of husbands in kadarzi were obtained through observation using check list. Data analysed with univariable and bivariable technique; statistical test used chi square (χ2 ) and multivariable analysis used logistic regression statistical test.Results: Knowledge of husbands on kadarzi was 63.2% belonged to high category and 36.6% belonged to low category. Attitude of husbands toward kadarzi was 53.2% belonged to strong category and 46.8% belonged to weak category. As much as 69.60% of families had not practiced kadarzi and 30.40% had practiced kadarzi. The result of statistical test showed that there were significant relationship between knowledge and attitude of husbands and behavior of kadarzi, wives’ level of education and activities and behavior of kadarzi (p<0.05).Conclusion: There was a siginifcant relationship between knowledge and attitude of husbands and behavior of kadarzi when control variables of wives’ education and activities were included in the analysis.